2018
DOI: 10.22271/ortho.2018.v4.i1i.81
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical and functional outcomes of unstable intertrochanteric femur fractures treated with long proximal femoral nail

Abstract: Introduction:The following study was conducted to examine the long term clinical, radiological and functional results of unstable intertrochanteric femur fractures treated with long Proximal Femoral Nail. Materials and Methods: This was a prospective, non-randomized study of 50 cases of intertrochanteric fractures of unstable variety treated by long Proximal Femoral Nail at the Department of Orthopedics, B J Medical College and Civil Hospital, Ahmedabad, between 2014 to 2016. Patients were undergoing primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…There was a female sex preponderance seen in our study. This is the same as in Dhar et al (9) and Zhang et al (10) studies, while Yadkika et al (8) , Daivesh et al (11) and Chang et al (12) , showed male sex preponderance. In this study, there was no significant correlation between sex and the final outcome.…”
Section: Discussionsupporting
confidence: 86%
“…There was a female sex preponderance seen in our study. This is the same as in Dhar et al (9) and Zhang et al (10) studies, while Yadkika et al (8) , Daivesh et al (11) and Chang et al (12) , showed male sex preponderance. In this study, there was no significant correlation between sex and the final outcome.…”
Section: Discussionsupporting
confidence: 86%